(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In modern era, maintainability is an important part for software development that covers approx. 70-75% of development cost of the software system. It can allow the customer to adapt the software quickly and easily in an agile manner. Object oriented software metrics plays an important role for the designing of software development. Its features can be categorized into the object oriented metrics and the hierarchies of the class. In this paper, a tool named as COIN can help for evaluating the maintainability factors of object oriented software system using metrics like cohesion, coupling, inheritance and other object oriented metrics as well as through which we can analyzed the all metrics for the software system for evaluating the maintainability factors and testability also.